Almost Bi-interior Ideal in Semigroups and Their Fuzzifications (European Journal of Pure and Applied Mathematics, 2022)
In this paper, we define the concepts of alomst bi-interior ideal and fuzzy almost bi-interior ideal in semigroups. Moreover, we prove that relation between almost bi interior ideal and fuzzy almost bi-interior ideal.
Keywords: bi-interior ideal; fuzzy bi-interior ideal; weakly bi-interior ideal; weakly fuzzy bi-interior ideal